Penyelesaian Masalah Transportasi menggunakan Transportation Optimality Complementary Method (Tocm) Dengan Zero Point Minimum Method (Zpmm) Dan Uji Optimalitas Midofied Distribution (Modi): Transportation Problem Solving Using the Transportation Optimality Complementary Method (TOCM) with the Zero Point Minimum Method (ZPMM) and Modified Distribution Optimality Test (MODI) - Hikmawati, Lia; Affandi, Pardi (Equiva Journal, 2025)
The transportation problem is a special type of linear programming that aims to minimize the total distribution cost from several sources to multiple destinations while satisfying supply and demand constraints. This study applies a combination of the Transportation Optimality Complementary Method (TOCM) and the Zero Point Minimum Method (ZPMM) to obtain an efficient initial solution, followed by an optimality test using the Modified Distribution Method (MODI). Three types of cases were analyzed: balanced transportation, excess supply (supply > demand), and excess demand (demand > supply). The results indicate that the TOCM–ZPMM method can produce an initial solution that is very close to the optimal result, making the optimization phase with the MODI method require fewer iterations. Therefore, this combination improves computational efficiency and provides accurate solutions, making it an effective alternative for solving transportation problems in logistics and distribution systems.